PENGARUH PERANGKAT PEMBELAJARAN BERBASIS MASALAH DAN KEMAMPUAN BERPIKIR KREATIF TERHADAP CAPAIAN KOMPETENSI MATAKULIAH FISIKA UMUM MAHASISWA JURUSAN FISIKA FMIPA UNIMED - Jurubahasa Sinuraya; Sehat Simatupang; Ida Wahyuni (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
This Study is a continuation of development research of previous year. The goals of this study are to test 1) differences in competence achievement of physics II between groups of users of the learning device based problem and users of conventional learning device 2) differences in competence achievement of physics II between high creative group and low creative group, and 3) effects of interactive learning device based problem with the ability to think creatively towards the achievement of general physics II competence. This research design is a 2x2 factorial. The population is physical education student class of 2014. Through sampling scluster techniques, set the experimental class and the control class. Each class consist of 24 peoples so the total number of samples is 48 peoples. Conclusion of research are : 1) there are differences in competence achievement of general physics II between the group using the learning device based problem and using the conventional learning device, 2) there are differences in competence achievement of general physics II between high creative group and low creative group, and 3) there are no interactive learning device based problem with the ability to think creatively towards the achievement of general physics II competence. Keywords: learning device, based problems, think creatively, and achievement of competence.